Surgical-orthodontic treatment in patients with Ehlers-Danlos syndrome: a report of two familial cases - Chapuis Hippolyte; Peyrolade Arnaud; Féki Ahmed; Clauss François; Bornert Fabien (EDP Sciences, 2020)
Introduction: Ehlers-Danlos syndromes (EDS) are a group of rare inherited connective tissue disorders that affect the synthesis and structure of collagen in a ubiquitous manner. The clinical presentation can vary according to the associated genetic mutation. The 2017 international classification of EDS describes 13 types of EDS. Observation: The first part of this paper describes the surgical-orthodontic treatment for two sisters affected by a common and familial form of EDS, with a follow-up period of 8 years. The main symptoms were agenesis, impacted teeth, and delayed eruptions. Discussion: The second part proposes a review of oro-dental manifestations and discusses therapeutic approaches for patients with EDS. Conclusion: EDS can affect the oro-dental region with numerous consequences. Recognition of clinical symptoms and radiological signs is essential to provide appropriate dental care. Moreover, complete clinical and radiological assessment can allow early diagnosis of EDS.